Age at menarche is associated with the prevalence of non‐alcoholic fatty liver disease later in life: 初潮年龄与成年后非酒精性脂肪性肝病患病风险相关. (23rd March 2016) - Lu, Jieli; Zhang, Jie; Du, Rui; Wang, Tiange; Xu, Min; Xu, Yu; Wang, Weiqing; Bi, Yufang; Li, Donghui; Chen, Yuhong; Ning, Guang
Abstract: Background: The aim of the present study was to investigate whether age at menarche is associated with non‐alcoholic fatty liver disease (NAFLD) later in life. Methods: The association between age at menarche and obesity, insulin resistance, and NAFLD after menopause was investigated in a cross‐sectional study of 4128 postmenopausal Chinese women; NAFLD was diagnosed by hepatic ultrasound and information regarding age at menarche was collected using an interviewer‐administered questionnaire. Results: Women with age at menarche <15 years had higher prevalence of overweight/obesity, insulin resistance, and NAFLD compared with women with age at menarche 15–18 or >18 years. Logistic regression revealed that women with earlier menarche had a higher risk for the age‐adjusted prevalence of overweight/obesity, insulin resistance, and NAFLD, whereas later menarche showed a weaker, but still significant, association with a lower prevalence of NAFLD. However, further adjustment for some variables and current body mass index (BMI) or homeostasis model assessment of insulin resistance (HOMA‐IR) attenuated the association between later menarche and a lower prevalence of NAFLD. A decreasing trend in the risk of NAFLD was seen across increasing levels of age at menarche (age‐adjusted P trend  < 0.001; multivariate‐adjusted P trend  < 0.001; multivariate + current BMI‐adjusted P trend  = 0.03; multivariate + HOMA‐IR‐adjusted P trend  = 0.06). Conclusion: Age at menarche is associated with the prevalence of NAFLD later in life, independent of BMI and insulin resistance. Abstract : Prevalence of non‐alcoholic fatty liver disease (NAFLD) stratified by age at menarche and body mass index (BMI; in kg/m 2 ).